Job search during the COVID-19 crisis - Hensvik, Lena; Le Barbanchon, Thomas; Rathelot, Roland (Journal of public economics, 2021)
•In Sweden, new vacancy postings drop by 40% during the 3 months after the COVID-19 outbreak.•Job seekers decreases their search intensity by 15% during the 3 months after the COVID-19 outbreak.•Vacancy-level tightness increases by 25% during the 3 months after the COVID-19 outbreak.•Job seekers redirect their search towards less severely hit occupations. This paper measures the job-search responses to the COVID-19 pandemic using real-time data on vacancy postings and job ad views on Sweden’s largest online job board. First, new vacancy postings drop by 40%, similar to the US. Second, job seekers respond by searching less intensively, to the extent that effective labour market tightness increases during the first three months after the COVID outbreak. Third, they redirect their search towards less severely hit occupations, beyond what changes in vacancies would predict. Overall, these job-search responses have the potential to amplify the labour demand shock.